Diagnosis and treatment of transnasal endoscopic optic canal decompression for traumatic optic neuropathy - Tu, Xiang; Xiong, Cheng; Qi, Hui; Ou, Yangming; Rao, Jing; Sun, Yueqi; Fan, Yunping; Liu, Guiqin (Frontiers in Neuroscience, 2023)
objective: To investigate the clinical efficacy and prognostic factors of transnasal endoscopic optic decompression in the treatment of traumatic optic neuropathy (TON). Methods: A retrospective analysis was performed on 13 TON patients in the Seventh Affiliated Hospital of Sun Yat-sen University and Shenzhen Eye Hospital in Shenzhen City (China) from June 2020 to April 2022. These patients had received transnasal endoscopic optic decompression, and hormonal and neurotrophic drugs were given after surgery. Visual acuity (VA) improvement was used as the criterion to judge clinical efficacy. Results: In a total of 13 patients, 13 injured eyes (12 men and 1 woman; mean age, 28.0 ± 11.8 years) received transnasal endoscopic optic decompression. After surgery, 9 patients had improved VA, whereas 4 patients failed to show any improvement, resulting in a total effective rate of 69.2%. Of the 6 patients with no light perception preoperatively, 3 had effective results after the operation, giving an effective rate of 50.0%. Of the 7 patients with residual light sensation preoperatively, 6 had effective results after the operation, giving an effective rate of 85.7%. Of the 10 patients operated on within 7 days after injury, 7 had effective results, giving an effective rate of 70%. Of the 3 patients injured and operated on after 7 days, 2 had effective results, giving an effective rate of 66.7%. Conclusions: Transnasal endoscopic optic nerve decompression is an effective treatment method for TON. The presence of residual light perception and the timing of surgery within 7 days are crucial to the prognosis.